1998
DOI: 10.1063/1.476618
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and macrophase separation in blends of reversibly associating one-end-functionalized polymers

Abstract: Phase diagrams for reversibly associating one-end-functionalized chain molecules ͑with an emphasis on hydrogen bonding͒ are determined by computer simulations of a cubic lattice model employing canonical and grand canonical Monte Carlo methods. Due to the relatively short chain lengths used, the stability of the homogeneous state is strongly enhanced compared to mean-field random phase approximation predictions. Characteristic phenomenon such as reappearing phases and macrophase separation into two phases, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
(36 reference statements)
2
32
0
Order By: Relevance
“…Theory has also predicted interesting behavior in supramolecular polymer systems; 1,[49][50][51] in particular, regions of macrophase separation, microphase separation, and disordered (miscible) phases are commonly observed. For supramolecular diblock copolymers, 1 several reentrant phase transitions are predicted at molecular weights where the binding energy between the hydrogen bonding end groups on immiscible homopolymers is nearly balanced with χN, where χ is the Flory-Huggins interaction parameter and N is the degree of polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Theory has also predicted interesting behavior in supramolecular polymer systems; 1,[49][50][51] in particular, regions of macrophase separation, microphase separation, and disordered (miscible) phases are commonly observed. For supramolecular diblock copolymers, 1 several reentrant phase transitions are predicted at molecular weights where the binding energy between the hydrogen bonding end groups on immiscible homopolymers is nearly balanced with χN, where χ is the Flory-Huggins interaction parameter and N is the degree of polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have recently demonstrated the synthesis of MHB random copolymers [6][7][8][9][10][11][12] or block copolymer-like materials. [13][14][15][16][17] In the case of MHB block copolymers, as the temperature of the polymer melt is increased, the bonds joining dissimilar blocks break to generate homopolymers that can then swell the microphase-separated domains and reversibly increase the overall domain spacing as much as 300%. 16 Additionally, polymeric systems utilizing strategically placed reversible binding groups provide potential beyond alternative processing methods.…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, polymeric systems utilizing strategically placed reversible binding groups provide potential beyond alternative processing methods. Recent theory 17,18 indicates that by carefully balancing polymer interactions with the strength and directionality of hydrogen-bonding groups chain-end-functionalized materials have the potential for widely varying structures and properties, all derived from a few simple building blocks. In order to fully take advantage of this potential, however, a model polymer system must be developed that shows the proper balance between phase separation (characterized by the Flory-Huggins parameter) and hydrogen-bonding strength at experimentally relevant temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions. [5][6][7][8][9][10] To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, [24][25][26] and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%